How do young students with different profiles of reading skill mastery, perceived ability, and goal orientation respond to holistic diagnostic feedback?. (July 2015) - Jang, Eunice Eunhee; Dunlop, Maggie; Park, Gina; van der Boom, Edith H.
One critical issue with cognitive diagnostic assessment (CDA) lies in its lack of research evidence that shows how diagnostic feedback from CDA is interpreted and used by young students. This mixed methods research examined how holistic diagnostic feedback (HDF) is processed by young learners with different profiles of reading skills, goal orientations, and perceived ability. HDF provides three learner profiles: learners' current skill mastery levels; self-assessed skill proficiency; and goal orientations. It also has a section for plans for future learning. A total of 44 Grades 5 and 6 students (aged 11–12) from two classrooms, their parents and teacher received individually customized HDF reports. Students' reading skill mastery profiles were determined based on the application of cognitive diagnostic modeling to their performance on a provincial reading achievement measure, while their perceived ability and goal orientation profiles were created by using self-assessment and goal-orientation questionnaires. Students and parents provided written responses to their HDF reports. The study findings show the dynamic influence of young students' profiles on the ways in which they perceive, interpret and use HDF. Students' responses to diagnostic feedback did not differ substantially across reading mastery levels; however, psychological factors most strongly impacted the efficacy of learner feedback processing. Furthermore, the result that it was not students' actual goal orientations but their perceived parent goal orientations that showed significant relationships with their skill mastery levels strongly indicates that young students' responses to HDF are likely to be influenced by broader learning environments, and such influences are further filtered through their own perceptions. Understanding students' interactions with diagnostic feedback is critical for maximizing its effect because their perceptions about ability and orientations to learning strongly influence the ways in which they process diagnostic feedback on their learning.